2011
DOI: 10.1021/am2007917
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monodisperse Fluorinated Silica Nanoparticles and Their Superhydrophobic Thin Films

Abstract: :Monodispersive silica nanoparticles have been synthesized via the Stöber process and further functionalized by adding fluorinated groups using fluoroalkylsilane in an ethanolic solution. In this process, six different sizes of fluorinated silica nanoparticles of varying diameter from 40 to 300 nm are prepared and used to deposit thin films on aluminum alloy surfaces using spin coating processes. The functionalization of silica nanoparticles by fluorinated group has been confirmed by the presence C-F bonds alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(115 citation statements)
references
References 36 publications
3
109
0
Order By: Relevance
“…The manufacturer of the RTV silicone specified that it contains mainly three different molecules: trimethoxymethylsilane, hexamethyldisilazane and octamethylcyclotetrasiloxane. The peaks at 800 and 1100 cm −1 correspond to the asymmetric stretching vibration of Si-O-Si group [38] and [42]. A peak approximately at −1 is due to the Si-O-C bond.…”
Section: (C) and (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturer of the RTV silicone specified that it contains mainly three different molecules: trimethoxymethylsilane, hexamethyldisilazane and octamethylcyclotetrasiloxane. The peaks at 800 and 1100 cm −1 correspond to the asymmetric stretching vibration of Si-O-Si group [38] and [42]. A peak approximately at −1 is due to the Si-O-C bond.…”
Section: (C) and (D)mentioning
confidence: 99%
“…Two peaks at 1150 and 910 cm −1 are due to Si-N bondings [43]. The peaks at 1400, 2950 and 3000 cm −1 were assigned to -CH3 [38] and [42] as silicone contains plenty of methylated groups (-CH3). The presence of -CH3 as well as -CH2 together reduces the surface energy and enhances the water contact angle to a surface that leads to the superhydrophobic properties.…”
Section: (C) and (D)mentioning
confidence: 99%
“…The absorption band at 961 cm −1 is attributed to -Si-OH [22]. After F-PMHS surface modification, there are two new absorption bands at 900 cm −1 and 2167 cm −1 corresponding to -Si-C and -Si-H of F-PMHS, respectively [23]. In addition, the intensity of absorption band at 2964 cm −1 is strengthen while that of absorption band at 961 cm −1 is weakened gradually with the increasing F-PMHS concentration.…”
Section: Ftir Characterizationmentioning
confidence: 97%
“…It is difficult to demonstrate the existence of amphiphobic-CF 3 groups by FTIR because its absorption bands are similar to those of -CH 3 [23]. So the characterization of XPS is carried out further.…”
Section: Xps Analysismentioning
confidence: 99%
“…Due to the versatile applications of superhydrophobic surfaces researchers all around the world is are continuously working in this field of research [2][3][4][5][6]. Our group is actively working in the fabrication of superhydrophobic surfaces on aluminum and other metal surfaces using different techniques [7][8][9][10][11][12][13][14][15][16][17]. For example, we have previously shown that copper surfaces can be made superhydrophobic by a simple one-step electrochemical process.…”
Section: Introductionmentioning
confidence: 99%